A Military-Centered Approach to Neuroprotection for Traumatic Brain Injury - Shear, Deborah; Tortella, Frank C. (Frontiers in Neurology, 2013)
Studies in animals show that many compounds and therapeutics have the potential to greatly reduce the morbidity and post-injury clinical sequela for soldiers experiencing TBI. However, to date there are no FDA approved drugs for the treatment of TBI. In fact, expert opinion suggests that combination therapies will be necessary to treat any stage of TBI recovery. Our approach to this research effort is to conduct comprehensive preclinical neuroprotection studies in military relevant animal models of TBI using the most promising neuroprotective agents. In addition, emerging efforts incorporating novel treatment strategies such as stem cell based therapies and alternative drug delivery approaches will be discussed. The development of a non-surgical, non-invasive brain injury therapeutic clearly addresses a major, unresolved medical problem for the Combat Casualty Care Research Program (CCCRP). Since drug discovery is too expensive to be pursued by DOD in the TBI arena, this effort capitalizes on partnerships with the Private Sector (Pharmaceutical Companies) and academic collaborations (Operation Brain Trauma Therapy Consortium) to study therapies already under advanced development. Candidate therapies selected for research include drugs that are aimed at reducing the acute and delayed effects of the traumatic incident, stem cell therapies aimed at brain repair, and selective brain cooling to stabilize cerebral metabolism. Each of these efforts can also focus on combination therapies targeting multiple mechanisms of neuronal injury.